Custom, Identity, and Migration: The Glocalization of Work Environments in the Global South - Bhardwaj, Neha (Journal of Global Economy, Business and Finance, 2026)
The workplace demographic has undergone significant changes over time, influenced by a combination of factors such as population needs, technological advancements, and evolving workplace requirements. Globalisation factored in immensely with the way workplaces were tailored, shifting from a local focus on both product and employee to a more global outlook. The benefits of doing so involve a more engaged workforce, as well as higher employee satisfaction deriving from the introduction of new policies regarding employee equality and wellbeing. Hence, over time, global companies have recognized the importance of promoting labour equality and creating inclusive workspaces. The paper elaborates on such measures taken by, and the importance of, companies in the creation of inclusive workplaces.